Technology-Facilitated Domestic Abuse in Political Economy: A New Theoretical Framework - Yardley, Elizabeth (Violence against women, 2021)
This article presents a new theoretical framework around technology-facilitated domestic abuse (TFDA) in identifying four distinct types of omnipresent behavior. Perpetrators are increasingly drawing upon networked technologies like smartphones, social media, and GPS trackers in monitoring, controlling, and abusing survivors. There is considerable academic literature developing in response to this. While this scholarship is valuable, this article argues that TFDA must be understood as a neoliberal manifestation of patriarchal legacies of misogyny and sexism. A failure to recognize this will serve to prioritize abusers’ freedom to do harm over rights of survivors to be protected from harm.